5 - Mobile Money and the Human Economy: Towards Sustainable Livelihoods for Zimbabwean Migrants in South Africa - Mavodza, Emma (Africa Development, 2019)
This article explores ways in which Zimbabwean migrants in South Africa send, receive and give money through mobile technological innovations. Specifically, the article looks at how the unbanked people access and manage money in their daily lives. Most of these migrants are undocumented and find it difficult to open accounts as financial institutions require certain specifications such as proof of residence, (local) identity cards, work permits, traceable physical addresses and three current consecutive months’ payslips. However, with the advent of mobile money, these migrants can easily relay money to Zimbabwe which records a high influx of remittances which are sustaining an ailing economy and improving the livelihoods of the people. The article also demonstrates ways in which the (un)banked are excluded or included in the transaction of money through social networks, kinship ties, solidarity relationships and other forms of non-monetary exchanges. In addition, it analyses the extent to which mobile money has impacted on social, economic and political relations of the unbanked. Using qualitative methodology, I also illustrate how mobile money improves the unbanked’s access to money and enhances the creation of a society with the attributes of a human economy with reduced inequalities.